ANALYSIS OF EFFECT OF EXCHANGE RATE, INFLATION, AND POWER PURCHASE ON DISTRIBUTION OF CREDIT IN COMMON CONVENTIONAL BANKS - Riani, Debora Diazka; Octavianus, Rony Joyo Negoro; Hutapea, Tommy Mora Hamonangan (Universitas Brawijaya, Indonesia, 2018)
This study aims to determine the macroeconomic effects seen from the exchange rate, inflation, and purchasing power to lending channeled by conventional banks. By this research is quantitative research with research type which used is causal research. The sampling in this study using purposive sampling method and found that the sample of this study is Bank BUKU 4. This study uses multiple linear regression analysis techniques. The results from the results of this study are when viewed partially, there are two variables that are not significant to the dependent variable, the exchange rate and inflation variables have a negative relationship toward the amount of loan disbursement and not significant. This applies to policies that the government and BI set to maintain the stability of the country's economic system. As for the variable purchasing power has a significant influence and has a negative relationship with the amount of loan disbursement. From the results of this study is expected to continue to maintain the macroeconomic situation in Indonesia in order to increase the growth of lending and the importance of supervision from the government to maintain the stability of macroeconomic conditions in Indonesia